Access to internal capital, creditor rights and corporate borrowing: Does group affiliation matter? - Thapa, Chandra; Rao, Sandeep; Farag, Hisham; Koirala, Santosh (Journal of Corporate Finance, 2020)
We examine whether the effect of increased creditor rights on corporate borrowing depends on firm's access to internal capital. By exploiting a creditor protection reform in India, empirical outcomes strongly indicate that strengthening of creditor rights leads to increased corporate borrowing among firms that have constrained access to internal capital compared to business group affiliated firms, which have relatively easier access to internal capital. Further, the increased corporate borrowing by firms with constrained access to internal capital, in the post-reform period, is associated with a greater expansion of real investments, improved operational performance, and better market valuation. Taken together, these findings indicate that expanding creditor rights may aid in improving allocative efficiency.